MENELUSURI FENOMENA BILLBOARD HAMPA - Farid Abdullah; Bambang Triwardoyo (Universitas Trisakti, 2017)
ABSTRACTThis article examines the billboard phenomenon in Jakarta were confirmed by the Kompas survey (October 29 to 31, 2016) against the benefits of the billboard. Billboards conditions present (2017) is contrast to the 1990s. The development of digital technologies such as double-edged sword and can not be inevitable. On the one hand facilitate human life, but on the other hand lethal for those who are not ready for acceleration. Studies of this article is descriptive - quantitative expose people's satisfaction advertisement billboard in Jakarta. Also society will certainly be an important consideration in making decisions and determine the way forward. This feedback is also very important for the Visual Communication Design profession in monitoring the development of design in the future.ABSTRAKTulisan ini mengkaji fenomena billboard di Jakarta diperkuat dengan hasil survey harian Kompas (29-31 Oktober 2016) terhadap manfaat reklame. Kondisi reklame masa kini (2017) berbeda dengan masa 1990-an. Perkembangan teknologi digital seperti pisau bermata dua dan tidak dapat terelakkan. Di satu sisi memudahkan kehidupan manusia, namun di sisi lain mematikan bagi mereka yang tidak siap akselerasi. Kajian pada artikel ini secara deskriptif - kuantitatif memaparkan kepuasan masyarakat terhadap reklame billboard di Jakarta. Masukan masyarakat tentu menjadi pertimbangan penting dalam mengambil keputusan dan menentukan langkah ke depan. Masukan ini juga sangat penting bagi profesi Desain Komunikasi Visual dalam mencermati perkembangan desain di masa mendatang.